Distribution patterns and habitat use of the smooth hammerhead shark (sphyrna zygaena) in the Atlantic Ocean - Santos, Catarina Casaca Neves dos (2018)
Tese de mestrado, Ecologia Marinha, Universidade de Lisboa, Faculdade de Ciências, 2017